PROTEIN KINASE INHIBITORY PROPERTIES OF EXTRACTS DERIVED FROM BOCCONIA FRUTESCENS AND GOMPHOCARPUS PHYSOCARPUS - Thomas, Kūpa‘aikekaiao; Zhang, Mengke; Reinicke, Justin; Parker, Jimmy; Ohora, Donna; Wall, Marisa M.; Songsak, Thanapat; Wongwiwatthananukit, Supakit; Chang, Leng Chee (Interprofessional Journal of Health Sciences, 2023)
Bocconia frutescens is an invasive shrub originally introduced to Hawai’i as an ornamental plant. Gomphocarpus physocarpus is a shrub that is native to southern Africa, also introduced to Hawai’i. These two plants were selected for study due to the possibility of alkaloid contents and biological activities. The objective of this study was to examine the protein kinase inhibitory activity (PKI) of crude methanol extracts derived from Bocconia frutescens and Gomphocarpus physocarpus using hyphae formation inhibition assay against Streptomyces 85E at concentrations of 20 μg/disk. Extracts that showed protein kinase inhibitory activity at this concentration were tested at lower concentrations. Results found that all B. frutescens extracts showed PKI activity, whereas none of the G. physocarpus showed biological activity. In addition, the presence of chelerythrine and berberine alkaloids in B. frutescens extracts were assessed during this study using thin layer chromatography (TLC) and liquid chromatography-massspectrometry (LC-MS) analysis. The results showed that both alkaloids were present in all B. frutescens extracts.